PEMANFAATAN APLIKASI WHATSAPP GROUP (WAG) SEBAGAI SARANA PEMBELAJARAN JARAK JAUH (PJJ) PADA SISWA KELAS IV (Studi Kasus Pembelajaran di Era Pandemi di SDN Kencana Indah II) - Darda Abdullah Sjam; Jaka Permana; Oktivia Indira Nurcahyanti (STKIP Subang, 2022)
This study aims to describe the use of the WhatsApp Group Application as a Distance Learning Media for Class IV Students at SDN Kencana Indah II, the obstacles that occur in the use of the WhatsApp Group Application as a Distance Learning Media for Class IV Students at SDN Kencana Indah II and the solutions implemented to overcome these obstacles. This study uses descriptive research with a qualitative approach. In this study, the subjects were Teachers, Students, and Parents of Class IV Students. The research data was collected through observation, interviews, questionnaires, and documentation studies. The results of the study indicate that teachers have used the WhatsApp Group application as a learning medium in supporting distance learning activities by utilizing various available features such as photo, video, document, telephone, and video call features. The ease is felt by the presence of the WhatsApp Group feature and also its easy use and can be used by various groups in teaching and learning activities, this is supported by the results of a questionnaire which states that 55% of respondents strongly agree with the ease of use of the WhatsApp Group application as a learning medium and 39% of respondents thers agree with the statement. Then in the implementation of the use of WhatsApp Group as a distance learning medium, there are several obstacles, such as signal interference, full cellphone memory, lack of interaction, difficulty knowing the seriousness of students' learning, lack of student motivation to learn, online learning support facilities, and difficulty understanding the material provided, as well as in this study describe the solutions carried out to overcome the obstacles that occur from the use of the WhatsApp Group application as a distance learning medium.